A descriptive study of African American deciduous dentition - Loren R. Lease (Dental Anthropology Association, 2013)
Descriptive studies of the deciduous dentition morphology have been presented as an inclusion in permanent dentition studies, the focus of archaeological populations or on specific traits within modern populations. The present study describes 25 morphological traits of deciduous dentition in two African American samples from Memphis, TN and Dallas, TX (N= 218), and a European American sample (N=100) from Cleveland, OH. These traits represent the most commonly used traits in population microevolution studies, describing various ancestral groups. Results indicate trait frequency variation between the two African American samples, as well as in comparison to European American samples. Traits varying in frequency between the two sample populations include maxillary lateral incisor shovel shape trait (69% vs. 46%), canine tuberculum dentale (40% vs. 22%), canine mesial ridge (3% vs. 7%), and maxillary posterior molar hypocone development (76% vs. 92%). Trait frequencies higher than found in previous studies include maxillary central incisor shovel shape trait (38%) and maxillary lateral incisor shovel shape trait (68%), canine tuberculum dentale (40%), maxillary molar complexity (20%), cusp six (33%) and seven (68%), and the Y-groove on the mandibular posterior molar (69%). Trait frequencies seen lower in previous studies include tuberculum dentale trait on both maxillary incisors (8% and 3%) and the hypocone development of the maxillary posterior molar (76%). The level of trait expression is informative when comparing populations, especially the molar traits. For example, Carabelli's pit/fissure is the most common trait expression in African American samples, unlike European American samples.